Desain Pembelajaran ADDIE (Analysis, Design, Development, Implementation, and Evaluation) E-Learning Pada Materi Sejarah Kebudayaan Islam - Nurul Azizah; Syarifah (Jurnal Pendidikan Islam, 2021)
The implementation of online learning or e-learning can be a solution during the COVID-19 pandemic, Although in practice, there are often problems. This happens because teachers and students are unfamiliar with e-learning learning, limited internet access, and the presentation of the material is less attractive to students. One attempt to solve the problem is by designing and planning lessons well because the design is the initial step in determining the successful implementation of learning. The results of this study are 1. The steps for designing the ADDIE models are a) the needs analysis and problem analysis stages b) designing the content of materials, media, and learning strategies, c) developing lesson plans and syllabus using the student centered Learning-Based approach, d) Application of design that is designed for e-learning teaching situation and e) test and validation by experts, 2) The results of the validity of the learning planning design based on the material validator get 3.49 results with good criteria and media validators get results, 3.62 with very good category, and 2) The results of student responses with very good answers to the design of learning media reached 78%.